Tool Condition Monitoring Of Drill Bit Wear Using Camera For Composite Assembly In Aerospace Manufacturing System - Ramzi, Ahmad Raiminor (2019)
The poor machinability of composite materials makes the tool condition monitoring (TCM) system is highly demanded for the drilling operation in aircraft manufacturing industry. It caused the drill bit to wear faster, reducing the tool life expectancy and increasing the manufacturing cost. It is important to replace the drill bit on time as the precautionary practice to avoid the expensive composite material from being damaged by the blunt drill bit. Therefore, TCM system provides a compact solution in monitoring, controlling and optimising the drill bit usage which will improve the machining quality indirectly. This research proposed a system to monitor the wear condition of drill bits used in composite machining which includes detection and measurement of wear. The detection concept is basically comparing the image of worn drill bit with the reference image of a brand new drill bit. The changes in the cutting edge region which indicating the amount of wear is measured in term of percentage by using image processing approach. Two samples of drill bits from real industry, FLE 190 and FLE 193 were used in the monitoring system testing. Based on the result, FLE 190 drill bit which is used to drill carbon fibre reinforced plastic - aluminium (CFRP/Al) stacks worn out at maximum flank wear percentage of 24.84 %. Meanwhile, FLE 193 drill bit is considered worn at 19.58 % when drilling glass fibre reinforced plastic - aluminium (GFRP/Al) stacks. The analysis shows that FLE 190 drill bit experienced a faster wear rate at average of 2.12 % per 100 holes while FLE 193 drill bit worn out at slower average rate of 0.46 % per 100 holes due to the different strength of the workpiece. The system is capable to monitor the drill bit flank wear and classify it into abrasive and adhesive wear mechanism. Besides, the illumination technique used enables the system to be used for various drill bit with different height and point angle. The output and contribution of this research proving that the direct optical monitoring system proposed is applicable for the industrial application.